Typologies of people’s preexisting political ideology and values would determine their post-pandemic mental health and political behaviors: Evidence from China - Pan, Shaojie; Xie, Xiaoqin; Xu, Linghong (Frontiers in Psychology, 2023)
The pandemic of COVID-19 has caused economic and social crisis across the world. Existing studies have shown that the uncertain social context has profoundly affected people’s life, triggering a variety of social psychological phenomena including the deterioration of mental health and the change of political behavioral patterns. However, little has been known about the differences in people’s pre-pandemic political ideology and their influences on people’s mental health and political behaviors after the pandemic. Using the secondary data from the 2018 and 2020 China Family Panel Studies, we measured nationalism tendencies, state performance ratings, social justice evaluation and life satisfaction of 29,629 adults before the pandemic. Using latent profile analysis (LPA), we examined the typologies of respondents’ political ideology and values. Five types emerged to identify respondents with different political ideology and values: Class-1) High nationalism tendency, country evaluation, social justice perception, and life satisfaction; Class-2) Low life satisfaction; Class-3) Moderate ratings; Class-4) Low nationalism tendency; Class-5) Low country evaluation, low social justice perception. We further explored the predicting roles of those typologies on people’s depressive symptoms and political engagement behaviors after the pandemic. We found that, after the pandemic, although the depressive symptoms of people with low life satisfaction (Class-2) and low country and society ratings (Class-5) eased, they still tended to have more severe depressive symptoms than the Moderate ratings group (Class-3). People with low life satisfaction (Class-2) were also less likely to follow political information than the moderate group (Class-3). Our research revealed how the psychology and behaviors of Chinese people with different political views changed when faced with uncertainty in social context. Further research needs to be carried out to depict how these changes occur.